Drug-nutrient cocrystallization-driven strategy towards self-assembly of milrinone and ferulic acid provides an exemplification in perfecting in vitro/vivo characteristics of anti-heart failure drugs. (17th May 2022) - Liu, Lu; Yu, Yue-Ming; Yu, Yu; Bu, Fan-Zhi; Wu, Zhi-Yong; Yan, Cui-Wei; Li, Yan-Tuan
Abstract : The in vitro / vivo properties of the anti-heart failure drug milrinone were optimized by cocrystallizing with a nutraceutical, ferulic acid. Abstract : A drug-nutrient cocrystallization-driven strategy has been established to highlight the superiority of nutraceutical ferulic acid (FEA) in perfecting the biopharmaceutical peculiarities of anti-heart failure drug milrinone (MLN). Taking the strategy as guidance, a novel cocrystal of MLN with FEA, namely MLN–FEA, is assembled and characterized, which reveals that the obtained solid form is a cocrystal of MLN molecule and FEA with the ratio of 1 : 1. There are milrinone–ferulic acid hydrogen-bonding couples, which are assembled into hydrogen-bonding chains in the crystal, and these chains connect the bilayer structure of MLN molecules gathering with π⋯π interactions of CO/CN groups with the pyridine rings to the whole three-dimensional framework. The combination of theoretical and experimental approaches proves that the aggregation motifs and structural features constituted by the introduction of ferulic acid in the crystal lattice have a significant effect on improving the solubility and permeability of the cocrystal. Interestingly, compared with the parent drug MLN, the ameliorated properties in vitro can be effectively transformed into a pharmacokinetic trait in vivo, revealing the extended half-life and raised bioavailability. Thereby, the current research not only supplies a novel solid form of MLN with potential commercial value, but provides some new opinions for the applications of nutritients in cardiotonic pharmaceutical cocrystals.